Pengaruh Budaya Organisasi, Kepuasan Kerja dan Komitmen Organisasi terhadap Kinerja Pegawai pada Kantor Badan Pertanahan Nasional Kota Padang - Dewirahmadanirwati, Dewirahmadanirwati; Nofrianti, Jeni (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of employee performance in government agencies, influenced by internal factors such as organizational culture, job satisfaction, and organizational commitment. The aim of this research is to determine the effect of organizational culture, job satisfaction, and organizational commitment on employee performance at the National Land Agency Office (Kantor Badan Pertanahan Nasional) of Padang City. This study employs a descriptive quantitative approach with a sample size of 53 respondents selected through purposive sampling from a population of 113 employees. The research instrument is a questionnaire that has been tested for validity and reliability. Data analysis techniques include descriptive analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression, t-test, F-test, and the coefficient of determination (R²) using SPSS version 26. The results indicate that organizational culture has a positive and significant effect on employee performance, while job satisfaction has a negative and significant effect. Organizational commitment is also found to have a positive and significant effect on employee performance. The F-test proves that the three independent variables simultaneously have a significant effect on employee performance, and no autocorrelation was found. These findings reinforce the importance of strengthening organizational culture and commitment as strategies for improving performance, while job satisfaction needs further analysis in the context of public sector organizations.